Common fixed point theorems for contractive mappings satisfying Φ-maps in S-metric spaces - Sedghi Shaban; Rezaee Mohammad Mahdi; Došenović Tatjana; Radenović Stojan (Acta Universitatis Sapientiae: Mathematica, 2016)
In this paper we prove the existence of the unique fixed point for the pair of weakly compatible self-mappings satisfying some Ф-type contractive conditions in the framework of S-metric spaces. Our results generalize, extend, unify, complement and enrich recently fixed point results in existing literature.